Addressing Barriers Newcomer Families Face When Obtaining Routine Childhood Vaccines in Alberta, Canada - Siobhan M. Wong King Yuen; Emily J. Doucette; Caitlin Ford; Madison M. Fullerton; Ginamaria Vetro; Amanda Koyama; Jia Hu; Cora Constantinescu (Vaccines)
Background/Objectives: As the newcomer population in Canada continues to grow, we aimed to collaborate with newcomer families arriving in an urban center in Alberta, Canada to identify strategies to overcome identified barriers newcomers face in obtaining routine childhood vaccines (RCVs). Methods: We recruited newcomers living in Calgary, Alberta to participate in a workshop utilizing the Nominal Group Technique (NGT) to develop solutions addressing barriers to obtaining RCVs. Ranking exercises helped identify the top-proposed interventions based on perceived impact and feasibility for implementation. Based on the identified need for translated vaccine resources, infographics on school-based vaccines were developed. The infographics were pilot-tested in a first-language focus group before the final product was translated into 10 different languages. Results: Consensus from 15 NGT workshop participants identified five key solutions to facilitate obtaining routine childhood immunizations: (1) Increasing access to reliable vaccine information; (2) Ensuring vaccine information and healthcare services are available in different languages; (3) Increasing vaccine appointment availability and optimizing the booking system for ease of navigation; (4) Increasing the role of family doctors in vaccine counseling and administration; (5) Streamlining vaccine record tracking. We developed infographics on the vaccines children in Alberta can receive through school-based vaccine programs and these were pilot-tested with 16 participants in a first-language (Arabic) focus group. Conclusions: The collaborative and iterative process of solution development with newcomers provided a platform for knowledge translation through the development of educational resources on school-based vaccines, addressing the information barrier that newcomers identified when accessing RCVs.